Platelet Aggregation on Extracellular Matrix: Effect of a Recombinant GPIb-Binding Fragment of von Willebrand Factor - Dardik, R; Ruggeri, Z M; Savion, N; Gitel, S; Martinowitz, U; Chu, V; Varon, D (Thrombosis and Haemostasis, 1993)
Platelets in whole blood incubated on extracellular matrix (ECM) produced by bovine corneal endothelial cells under oscillatory flow conditions demonstrate extensive aggregate formation. Since both platelet-subendothelium and platelet-platelet interactions are mediated by von Willebrand factor (vWF), we used this system to examine the effect of a recombinant GPIb-binding fragment of vWF (designated RG12986), comprising residues 445-733 of the native vWF subunit, on platelet reactivity with ECM. The seven cysteines present in the RG12986 fragment were reduced and alkylated in order to achieve a monomeric conformation. The recombinant vWF fragment binds to unstimulated platelets in the absence of exogenous modulators. When added to platelet-rich plasma, it inhibits ristocetin-induced platelet agglutination. Binding of 51Cr-labeled platelets in reconstituted whole blood to ECM was inhibited by RG12986 in a dose dependent and saturable manner, with IC50 of 4 μM and maximal inhibition (about 70%) at 6 μM. Scanning electron microscope (SEM) analysis showed that addition of RG12986 to whole blood significantly inhibited platelet aggregation on ECM. The extent of inhibition observed with RG12986 at a final concentration of 4 μM was similar to that obtained with the cell adhesion peptide RGDS at the concentration of 0.1 mM. The ability of the RG12986 fragment to inhibit platelet aggregation on ECM is in agreement with the concept that blockade of vWF-GPIb interaction may inhibit further events leading to activation of the glycoprotein IIb/IIIa (GPIIb/IIIa) complex and subsequent thrombus formation.